Technical effeciency in maize production by small-scale farmers in Ga-Mothiba, Limpopo Province, South Africa - Baloyi, Rebecca Tshelambilu (University of Limpopo (Turfloop Campus), 2011)
Maize is the most important cereal crop grown in South Africa. This crop is produced throughout the country under diverse environments. The study only focuses on the technical efficiency because it is an important subject in developing agriculture where resources are limited, but high population growth is very common. Technical efficiency is the ability of a farmer to obtain output from a given set of physical inputs. Farmers have a tendency of under and/or over- utilising the factors of production. The main aim of this study was to analyse the technical efficiency of small-scale maize producers in Ga-Mothiba rural community of Limpopo Province. The objective of the study was to determine the level of technical efficiency of small- scale maize producers and to identify the socio-economic characteristics that influence technical efficiency of small-scale maize producers in Ga-Mothiba. Purposive and Snowball sampling techniques were used to collect primary data from 120 small-scale farmers. Cobb-Douglas production function was used to determine the level of technical efficiency and Logistic regression model was used to analyse the variables that have influence the technical efficiency of maize production. Cobb-Douglas results reveal that small-scale farmers in Ga-Mothiba are experiencing technical inefficiency in maize production due to the decreasing return to scale, which means they are over-utilising factors of production. Logistic regression results indicate that out of 13 variables included in the analysis as socio-economic factors, 10 of them (level of education, income of the household on monthly basis, farmer`s farming experience, farm size, cost of tractor hours, fertiliser application, purchased hybrid maize seeds, membership to farmers` organisation, is maize profitable) were found to be significant and 3 (gender, age and hired labour) are non-significant. However, farm size was found to be the most significant variable at 99% level, showing a positive relationship to small- scale maize producer`s technical efficiency. Therefore, it is recommended that government should do the on-farm training since farmers mainly depend on trial and error and farmers` should have access to enough arable land and tractor services. However, farmers need to be trained on matters relating to fertiliser application, on the amount of seeds a farmer should apply per ha, and the importance of using hybrid seed.
Thesis (M.Sc. Agric.) --University of Limpopo, 2011
Keywords: Maize production; Production efficiency; 635.67; Corn -- Organic; Corn -- Seeds -- Production (Biology)